Uniportal Robotic Lobectomy and Lymphadenectomy for Invasive Lung Cancer: A Novel Approach and Perioperative Outcomes - Shengcheng Lin; Xiangyang Yu; Yafei Xu; Yu Xin; Jie He; Zhentao Yu; Hongbo Zhao; Chenglin Yang; Kai Ma (Thoracic Cancer)
ABSTRACT Background Multiport robot‐assisted thoracoscopic surgery (mRATS) has been comprehensively evaluated for its clinical efficacy in numerous studies. Nevertheless, the safety and feasibility of uniportal robotic lobectomy and lymphadenectomy require further validation. Methods The clinical data of 34 consecutive patients with lung cancer who underwent improved uniportal robotic‐assisted thoracoscopic surgery (uRATS) at our hospital between November 2023 and June 2024 were reviewed retrospectively. Camera‐centered uRATS was conducted using the da Vinci Surgical Xi system (Intuitive Surgical Inc., 1266 Kifer Road, Sunnyvale, CA 94086, USA). Descriptive statistics are expressed as numbers with percentages for categorical data or medians (ranges) or means with standard deviations for continuous data. Results Improved uRATS lobectomy and lymphadenectomy were conducted in 34 patients with postoperative pathology‐diagnosed invasive lung cancer. Among the patients, the median number of lymph nodes dissected was 24.5 (range 10–42), and the median number of stations with lymph nodes dissected was 8 (range 6–11). The median durations of the operation and the uRATS procedure were 200 min (range, 142–330 min) and 140 min (range, 80–242 min), and the median intraoperative blood loss volume was 20 mL (range, 10–100 mL), respectively. All postoperative complications, including pneumonia (2/34, 5.8%), air leakage > 5 days (2/34, 5.8%), prolonged wound healing (1/34, 2.9%), and arrhythmia (1/34, 2.9%), were graded as Clavien–Dindo grades I–II. There were no cases of wound infection or postoperative 30‐day mortality. Conclusion The safety and feasibility of uRATS lobectomy and lymphadenectomy using the da Vinci Surgical Xi system have been preliminarily validated.